Early public banks - William Roberds; François R. Velde (Federal Reserve Bank of Atlanta, 2014)
Publicly owned or commissioned banks were common in Europe from the 15th century. This survey argues that while the early public banks were characterized by great experimentation in their design, a common goal was to create a liquid and reliable monetary asset in environments where such assets were rare or unavailable. The success of these banks was, however, never guaranteed, and even well-run banks could become unstable over time as their success made them susceptible to fiscal exploitation. The popularization of bearer notes in the 18th century broadened the user base for the public banks' money but was also accompanied by increased fiscal abuse. Wartime demands of the Napoleonic Era resulted in the reorganization or dissolution of many early public banks. A prominent exception was the Bank of England, whose adept management of a fiscally backed money provided a foundation for the development of central banks as they exist today.
Keywords: E58; N13; 330; central banks; exchange banks; public banks